2006
DOI: 10.1136/ard.2005.041103
|View full text |Cite
|
Sign up to set email alerts
|

Finnish HLA studies confirm the increased risk conferred by HLA-B27 homozygosity in ankylosing spondylitis

Abstract: HLA-B27 homozygosity is associated with a moderately increased risk of ankylosing spondylitis compared with HLA-B27 heterozygosity. HLA-B27 positive cases had an earlier age of onset of ankylosing spondylitis than HLA-B27 negative cases and were more likely to develop AAU. HLA-DRB1 alleles may influence the age of symptom onset of ankylosing spondylitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
3
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 32 publications
8
51
3
6
Order By: Relevance
“…This finding has been supported by the results obtained in different ethnic groups (Brown, et al, 1998a;Jaakkola, et al, 2006;Kchir, et al, 2010;Mahfoudh, et al, 2011;Ploski, et al, 1995;SaidNahal, et al, 2002;Sims, A M, et al, 2007). HLA-DRB1 was found to have a strong association with AS.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding has been supported by the results obtained in different ethnic groups (Brown, et al, 1998a;Jaakkola, et al, 2006;Kchir, et al, 2010;Mahfoudh, et al, 2011;Ploski, et al, 1995;SaidNahal, et al, 2002;Sims, A M, et al, 2007). HLA-DRB1 was found to have a strong association with AS.…”
Section: Introductionsupporting
confidence: 79%
“…A Finnish report proposed that, in this specific population, the HLA-DRB1 alleles do not seem to play a strong role in AS susceptibility , but may influence the age of symptom onset (Jaakkola, et al, 2006). The results, in this casecontrol study, are limited due to the sample size.…”
Section: Introductionmentioning
confidence: 41%
“…56 Compared with B27-negative cases, B27 carriers have previously been demonstrated to have onset of symptoms at an earlier age. 27,57,58 In the current study, there were no B27-negative cases, perhaps explaining the lack of association seen.…”
Section: Discussionmentioning
confidence: 47%
“…This implies a risk of developing AS 3-fold higher than in heterozygous counterparts 7 . The consensus sequence obtained has shown that the individual has the HLA-B*27:90:01 subtype, for which there are no prior studies; but we may propose a possible link to AS.…”
Section: To the Editormentioning
confidence: 99%